If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 29 = 4r + -7 Reorder the terms: 29 = -7 + 4r Solving 29 = -7 + 4r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-4r' to each side of the equation. 29 + -4r = -7 + 4r + -4r Combine like terms: 4r + -4r = 0 29 + -4r = -7 + 0 29 + -4r = -7 Add '-29' to each side of the equation. 29 + -29 + -4r = -7 + -29 Combine like terms: 29 + -29 = 0 0 + -4r = -7 + -29 -4r = -7 + -29 Combine like terms: -7 + -29 = -36 -4r = -36 Divide each side by '-4'. r = 9 Simplifying r = 9
| -4+8a=-4 | | 5x+2x=6x-9 | | 13=3b+22 | | 6x+1=12x+17 | | 17x+12x-4=42 | | c(c-4)=21 | | 15s^3+25s^2-60s= | | -2m+4m+5=-3 | | 16-4t=4t | | 9x^2+28x+52=0 | | 17x-2(3x+4)=20 | | 2(6+3)= | | -13=x-7 | | x^2-24x+24=0 | | .15x-3.2=.5(x-5) | | 3x-4=2(7-x) | | 48-4t=4t | | 3(y-7)= | | (4x-2)=-1+2x | | 5-3(2x+9)=50 | | 0.4(x+90)+0.2x=45 | | X^2+4x-169=0 | | -5x+6=9-6x | | 9+5a=-26 | | t-22=-23 | | 8n-8=5n+7 | | -16t^2+40t-65=0 | | -16t^2+40t+65=0 | | 1.5(4d-2)=d+5 | | 4x-2=-6+5x | | 2x^2-48x+48=0 | | n-3=17-4n |